(untitled) (Innovaciones Educativas, 2023)
This systematization is related to the development of the multimedia "Planeta Planta" (in Spanish), a proposal that is part of the management of technological resources for distance teaching and learning of the General Botany course of the Natural Resources Management career of the Universidad Estatal a Distancia (UNED), Costa Rica. The first stage of the project included a diagnosis of the factors that affected student performance in the General Botany course in 2017. Based on the results of the diagnosis, the multimedia “Planeta Planta” was created, based on a constructivist paradigm and a cognitivist epistemological approach to promote meaningful learning. Multimedia is characterized by containing a variety of training activities, concept maps, images of plant anatomical structures, conceptual diagrams, and videos on plant physiological processes, among other resources. The validation of the product was carried out with students and teaching experts. Both groups considered that “Planeta Planta” is an educational resource with great usability and that it can increase motivation towards learning botany.